Monitoring of Unhatched Eggs in Hermann’s Tortoise (Testudo hermanni) after Artificial Incubation and Possible Improvements in Hatching - Alenka Dovč; Mateja Stvarnik; Renata Lindtner Knific; Gordana Gregurić Gračner; Igor Klobučar; Olga Zorman Rojs (Animals, 2021)
The causes of embryonic mortality in Hermann’s tortoises (Testudo hermanni) during artificial incubation were determined. Total egg failure at the end of the hatching period was investigated. The hatching artefacts represented 19.2% (N = 3557) of all eggs (N = 18,520). The viability rate of incubated eggs was 80.8%. The eggs, i.e., embryos, were sorted according to the cause of unsuccessful hatching and subsequently analyzed. Some of the eggs were divided into two or more groups. Unfertilized eggs were confirmed in 61.0%, infected eggs in 52.5%, and eggs in various stages of desiccation in 19.1%. This group also included mummified embryos. Pseudomonas aeruginosa, Bacillus sp., Purpureocillium lilacinum, and Escherichia coli were frequently confirmed in infected eggs. Embryos were divided into three groups: embryos up to 1.0 cm—group 1 (2.2%), embryos from 1.0 cm to 1.5 cm—group 2 (5.4%) and embryos longer than 1.5 cm—group 3 (7.3%) of all unhatched eggs. Inability of embryos to peck the shell was found in 1.3%. These tortoises died shortly before hatching. Embryos still alive from the group 2 and group 3 were confirmed in 0.7% of cases. Dead and alive deformed embryos and twins were detected in the group 3 in 0.5% and 0.1% of cases, respectively. For successful artificial hatching, it is important to establish fumigation with disinfectants prior to incubation and elimination of eggs with different shapes, eggs with broken shells, and eggs weighted under 10 g. Eggs should be candled before and periodically during artificial incubation, and all unfertilized and dead embryos must be removed. Heartbeat monitor is recommended. Proper temperature and humidity, incubation of “clean” eggs on sterile substrate and control for the presence of mites is essential. Monitoring of the parent tortoises is also necessary.